LEGAL VALIDITY OF SMART CONTRACTS FOR INVESTMENT PURPOSES: ANALYSIS OF INDONESIA’S LEGAL POLITICS AND EMERGING CHALLENGES - Agustianto, Agustianto; Situmeang, Ampuan (Masalah-Masalah Hukum, 2025)
The rapid development of digital technology has significantly transformed various economic sectors, particularly through the emergence of digitized contracts, including electronic contracts and smart contracts. These innovations are especially impactful in the investment sector, providing enhanced speed, security, and efficiency. As the Indonesian economy becomes increasingly integrated with digital technology, the role of electronic and smart contracts becomes crucial, necessitating adaptations in the country’s legal framework. Indonesia's legal system has responded with regulatory reforms, such as amendments to the Electronic Information and Transactions Law, aiming to address the needs of the digital economy. However, the pace of legal adaptation has raised concerns, particularly regarding the timely recognition and support for smart contracts, which are poised to revolutionize investment practices by automating transactions and reducing the reliance on intermediaries. Despite efforts to regulate electronic systems, Indonesia’s legal politics have struggled to keep up with the demands of these technological advancements, leading to gaps in the legal support for digitized contracts. This paper analyzes the intersection of Indonesia’s legal politics and the evolving landscape of investment, focusing on how the legal framework can better accommodate the integration of electronic and smart contracts. The study emphasizes the need for a comprehensive legal structure that fosters the growth of digital investment, providing legal certainty and protecting stakeholders. It ultimately proposes a model to support the future of investments, integrating legal clarity, regulatory adaptation, and industry collaboration to ensure that Indonesia’s legal framework can effectively support the evolving digital economy.